"A Nation at Bay": Ruth Farnham’s and Douglas Walshe’s Accounts from the Macedonian Front - Spremić Končar, Milica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This paper analyses two war travelogues from World War I whose authors served in the Serbian Army on the Macedonian front, Ruth Farnham’s A Nation at Bay: What an American Woman Saw and Did in Suffering Serbia and Douglas Walshe’s With the Serbs in Macedonia. Farnham’s duty was to take charge of the medical stores brought to Serbia from various English and American sources and Walshe was a driver in a Light Supply and Ammunition Column of Ford vans attached to the Serbian Army. Apart from offering detailed descriptions of their duties, Farnham and Walshe convey through their travelogues a very favourable picture of Serbia and its people, thus distancing themselves from the discourse of Balkanism, predominant in Great Britain and the United States during World War I. With due respect they write about Serbian soldiers, their ethics and humane attitude towards the Austrian and Bulgarian prisoners of war, whereas they do not hesitate to condemn the Allies’ treasonous response towards the Serbian Army in times of its greatest need. Having come to the Macedonian front to learn about Serbia and help it, Ruth Farnham and Douglas Walshe can be said to have challenged the negative reputation Serbia had in the British and American public. Their war travelogues clearly show that what they saw and experienced is in many ways incongruous with the then predominant discourse of Balkanism. That is why Farnham reveals to her reader that she feels ”the highest regard for that brave little nation, Serbia, and its gallant and heroic people” and Walshe ends his book in a simple and memorable sentence: ”It has been a privilege to serve them”.